I love you - Sirett, Dawn (London Dorling Kindersley Limited, 2017)
Baby Touch and Feel I Love You is a fun DK baby book that helps little ones learn new words. With touchy-feely pictures and word labels, it makes an ideal baby gift. Baby Touch and Feel I Love You contains stunning photos with foil or textured areas that expand your baby's senses, while the simple visuals and labels promote language skills. From shiny love hearts beside a little girl hugging her toy to a baby with a fleecy heart on his vest, you can introduce your baby to the concept of love with touch and feel textures. All this is packed in a handy, small format that's just perfect for preschoolers to hold, and helps develop their fine motor skills
Picture Book
Keywords: Love -- Juvenile literature; Love -- Pictorial works -- Juvenile literature; Textured books -- Specimens